2005
DOI: 10.1111/j.1740-8261.2005.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

RADIOGRAPHIC ANATOMY OF THE THORAX AND ABDOMEN OF THE COMMON MARMOSET (CALLITHRIX JACCHUS)

Abstract: A standard radiographic procedure was developed for the thorax and abdomen in the common marmoset. A description and reference values for the corresponding radiographic anatomy are given. Radiographs were obtained from 17 anaesthetized healthy mature marmosets ranging from 1.5 to 9 years and 328 to 506 g. Left-to-right lateral recumbent and ventrodorsal whole-body radiographs made at end inspiration are recommended. Images of the heart, lungs, liver, gastric axis, and at least one kidney could be evaluated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
55
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 13 publications
13
55
1
Order By: Relevance
“…This value was also lower than the VHS measured for the tamarin (9.42±0.44v) (Wagner & Kirberger 2005), porcupine (Black et al 2011) and bat (9.7±0.5v) (Gardner et al, 2007), but greater than that observed in ferrets (5.39±0.45 -LL projection) (Onuma et al 2009). The AB/H and CD/H ratios were studied in bats (Gardner 2007) and the AB/CD ratio in the porcupine (Black et al 2011).…”
Section: Discussionmentioning
confidence: 51%
“…This value was also lower than the VHS measured for the tamarin (9.42±0.44v) (Wagner & Kirberger 2005), porcupine (Black et al 2011) and bat (9.7±0.5v) (Gardner et al, 2007), but greater than that observed in ferrets (5.39±0.45 -LL projection) (Onuma et al 2009). The AB/H and CD/H ratios were studied in bats (Gardner 2007) and the AB/CD ratio in the porcupine (Black et al 2011).…”
Section: Discussionmentioning
confidence: 51%
“…Except dog and cat, a similar standardize study has been reported for ferrets (mean, 5.27v) [8]. However, no studies have examined monkey VHS other than in the common marmoset (mean  SD: 9.42  0.44) [10].…”
mentioning
confidence: 69%
“…Furthermore, VHS is known to be increased in coughing dogs compared with non-coughing dogs [2]. In non human primates, only one report has described VHS in the common marmoset (9.42  0.44v) [10]. In this study, we investigated normal VHS as a reference in the growth period of the Japanese macaque (Macaca fuscata).…”
mentioning
confidence: 99%
“…For nonhuman primates the values of 9.42±0.44v have been suggested for Callithrix jacchus (Wagner & Kirberger 2005), 10.7±0.69v for Aotus spp. (Knowlen et al 2013), 9.63±0.0.45v for Chlorocebus sabaeus (Young et al 2013) and 9.12±0.63v for Cebus apella (Alves et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although innumerable studies have been designed to establish both the assessment criteria and the definition of the morphometric parameters for several monkey species, such as Macaca nigra and Macaca tonkeana (Schillaci et al 2009(Schillaci et al ,2010, Macaca mulatta, Macaca fascicularis (Schillaci et al 2010), Callithrix jacchus (Wagner & Kirberger 2005) and the Rhesus monkey, only one study was found in the literature on the morphological aspects of the thoracic cavity in the tufted capuchin (Alves et al 2012).…”
Section: Introductionmentioning
confidence: 99%